Analysis of Wind Power Potential in Samiang Bay, Kotabaru, South Kalimantan - Fahrur Aslami; Elysa Nensy Irawan; Mohammad Muntaha; Suyatno; Mochamad Sahal (UIR PRESS, 2023)
This research was conducted to determine the potential for wind power from the Tamiang Bay area, Kotabaru, South Kalimantan. This study uses data on the average daily wind speed in Tamiang Bay with latitude -4.058883°, longitude 116.050259° obtained from the European Center for Medium-Range Weather Forecasts (ECMWF). Based on the analysis that has been done, the average daily wind speed in Tamiang Bay is 4 m/s for a height of 10 m and 5.98 m/s for a height of 50 m. Through the assumption that using a Gamesa G114-2.5 MW wind turbine with a tower height of 80 m, in one year, the Tamiang Bay area has the potential to produce 2646.58 MWh of wind power. Thus, the Tamiang Bay area is said to be very potential for wind power development.